Math, asked by Soumaditya04, 1 year ago

factorise the above question

Attachments:

Answers

Answered by Astrobolt
1
Hello there!
______________________________

You can factorise the given question as follows:

 = 2(ab + cd) - {a}^{2} - {b}^{2} + {c}^{2} + {d}^{2} \\ = {c}^{2} + 2cd + {d}^{2} - {a}^{2} + 2ab - {b}^{2} \\ = {(c + d)}^{2} - {(a - b)}^{2} \\ = (c + d + (a - b))(c + d - (a - b)) \\ = (c + d + a - b)(c + d - a + b)
Hence we have factorised the given equation!
_______________________________

Hope this helps!

Astrobolt: okay thanks
Similar questions